A review on the sustainability of thermal treatment for contaminated soils. (October 2019) - Ding, Da; Song, Xin; Wei, Changlong; LaChance, John
Abstract: Sustainable remediation is a goal in the remediation industry. Thermal treatment can remediate contaminated sites quickly and reliably, but its energy-intensive nature and potential to damage soil properties make it seemingly not sustainable. This review evaluates the potential for thermal treatment to become a sustainable remediation technology based on a comprehensive analysis of the scientific literature. The fundamentals, advantages, and limitations of single thermal treatment technologies are summarized. The compatibility and advantages of thermal treatment coupled with thermal, physicochemical, or biological technologies are reviewed. The results suggest that ingeniously designed coupled technologies can improve the availability and removal efficiency of contaminant, suppress the production of toxic byproduct, and reduce the required heating temperature and energy input. The sustainability of thermal treatment is then discussed from the perspectives of energy efficiency and land reuse. Approaches for improving energy efficiency include applying solar energy-based technologies, smoldering-based technologies, and coupled technologies. For land reuse, heating below 250 °C has negligible adverse impacts on most soil properties, and can increase nutrient availability and release dissolved organic carbon to support the growth of microorganisms and plants. Heating above 250 °C can significantly reduce soil organic matter and clay content, which decreases the soil cation exchange capacity and water holding capacity, and consequently damages the soil fertility. Some restoration strategies are also proposed for the recovery of soil quality. In addition, thermally remediated soil is considered to be a good candidate as an engineering medium for construction. This review concludes with an outlook of future research efforts that will further shift thermal treatment toward sustainable remediation. Graphical abstract: Image 1085 Highlights: Thermal treatment, as well as thermal-coupled technologies, are reviewed. Approaches for improving energy efficiency are summarized. A threshold of 250 °C was chosen to define how heating alters soil properties. Perspectives on future research are provided. Abstract : Thermal treatment for contaminated soils holds great potential as a sustainable remediation technology in terms of energy efficiency and land reuse.